Corrections to "Balancing the Energy Consumption and Latency of Over-the-Air Firmware Updates in LoRaWAN" - Borkotoky, Siddhartha S. (IEEE transactions on industrial informatics, 2025)
In [1], there are errors in two equations. In (5), the variable “A” was mistakenly included in the final expression. In (13) and (14), a multiplicative factor was missing in both equations.